Do Trade Agreements Stimulate International Trade Differently? Evidence from 296 Trade Agreements - Tristan Kohl; Steven Brakman; Harry Garretsen (Center for Economic Studies and ifo Institute (CESifo), 2013)
In a seminal paper, Rose (2004) found that the assumed positive impact of the WTO on international trade was questionable. This finding has been scrutinized and modified in subsequent research, using different datasets, econometric methods and separating the WTO from other forms of trade agreements. A key characteristic of this literature is the rather simplistic way in which trade agreements are treated whereby all trade agreements are lumped together. Trade agreements come, however, in many different forms and shapes. This paper addresses these differences in trade agreements. Using a unique database of 296 trade agreements, we distinguish 17 trade-related policy domains, 9 indicators of institutional quality and indicate whether the agreements contain legally enforceable commitments. This extensive and novel taxonomy of trade agreements enables us to allow for the possible heterogeneity of the impact of trade agreements on international trade. Using a gravity model, we find that trade agreement heterogeneity indeed matters for international trade, both positively and negatively.
Keywords: F13; F15; 330; trade agreements; gravity model; international trade